2023
DOI: 10.3390/min13081055
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Fe-Bearing Phases from Commercial Colombian Coal Ash

Abstract: High amounts of coal combustion products, such as fly ash and bottom ash, are generated every year; however, only 64% are used, which means that a significant part is landfilled despite containing valuable materials such as ferrospheres, which may be used as catalysts, substituting critical raw materials (e.g., platinoids). In commercial coals, pyrite contents are reduced as a pre-combustion S-emissions control measure, so low amounts of ferrospheres are expected in the respective ashes. However, given the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…In the processes of coal beneficiation and coal combustion in thermoelectric power stations (TPSs), several major waste products are generated, namely coal slurry, associated host rocks, bottom ash, and fly ash. It is well known that the detailed knowledge about the mineralogy and inorganic chemistry of these products has important fundamental, technological [1][2][3][4][5][6][7][8][9], and ecological [10][11][12][13][14][15] significance. Therefore, valuable information on the inorganic composition of coals and their combustion products has been summarized in several monographs [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the processes of coal beneficiation and coal combustion in thermoelectric power stations (TPSs), several major waste products are generated, namely coal slurry, associated host rocks, bottom ash, and fly ash. It is well known that the detailed knowledge about the mineralogy and inorganic chemistry of these products has important fundamental, technological [1][2][3][4][5][6][7][8][9], and ecological [10][11][12][13][14][15] significance. Therefore, valuable information on the inorganic composition of coals and their combustion products has been summarized in several monographs [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the origin of the hard coal, ash and other coal combustion residue (CCR) properties can vary significantly both in terms of calorific value and the presence of potential impurities [4,[9][10][11]. Leaching studies should also give some information about the possibilities of potential hazards associated with the extraction of toxic metals and their penetration into the soil and, in turn, into plants and the human food chain [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical analysis, especially the determination of elements important for their strategic significance and human and environmental safety, is a vital part of scientific research as well as commercial analysis. There are several instrumental methods routinely utilized in determining the minor (0.1-1%) and trace (<0.1%) elements of CCRs: inductively coupled plasma mass spectrometry, ICP-MS; inductively coupled plasma optical emission spectroscopy, ICP-OES; X-ray fluorescence, XRF; and the less commonly used single-element atomic absorption spectroscopy, AAS [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding catalyst support materials, it is crucial to improve studies based on alternative low-cost materials coming from recycling streams such as coal fly ash (FA), which are mainly composed of aluminosilicate glass and minor amounts of other materials, including Fe-rich particles such as ferrospheres [28,29] that are easily recovered via magnetic separation [2][3][4]. For example, Gadore and Ahmaruzzamn [30] reviewed the use of FA-based nanocomposites as effective photocatalysts for water remediation; Saputra and co-authors [31] prepared a Co-supported fly ash catalyst to promote phenol oxidation and observed a total degradation after 90 min at 45 • C; Yusuff et al [32] used FA-supported ZnO as a catalyst in biodiesel production from used oil and obtained an 83.2% yield after 180 min at 140 • C; Dong et al [33] used coal fly ash as a Ni-Re catalyst support for CO 2 methanation.…”
Section: Introductionmentioning
confidence: 99%